2011
DOI: 10.1007/s00595-011-0050-3
|View full text |Cite
|
Sign up to set email alerts
|

Stent strut penetration during thoracic endovascular aortic repair: report of a case

Abstract: We experienced a serious complication of proximal stent strut penetration (PSSP) during thoracic endovascular aortic repair in a 74-year-old man who underwent two-stage hybrid treatment for a distal arch thoracic aortic aneurysm. First, a debranching right common carotid-left common carotid-left subclavian artery bypass was performed. Second, a TALENT Thoracic Stent Graft (Medtronic, Tokyo, Japan) was inserted at Zone 1 (Ishimaru). At deployment, a proximal bare strut accidentally everted and penetrated the ao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…We performed coil embolization of the LSA for a type-2 endoleak in five patients. Localized intramural hematoma of the aortic wall developed in one of the patients with a TALENT thoracic stent graft, caused by penetration of a proximal bare stent [5]. This patient was treated conservatively.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…We performed coil embolization of the LSA for a type-2 endoleak in five patients. Localized intramural hematoma of the aortic wall developed in one of the patients with a TALENT thoracic stent graft, caused by penetration of a proximal bare stent [5]. This patient was treated conservatively.…”
Section: Resultsmentioning
confidence: 98%
“…However, this proximal stent also carries a risk of bare-spring eversion. In the present series, one patient suffered a localized intramural hematoma of the aortic wall, caused by penetration of the proximal stent [5]. Kasirajan et al [21] reported misaligned deployments of the TALENT at a rate of 0.1%.…”
Section: Discussionmentioning
confidence: 95%
“…In the peripheral vascular intervention field, the rate of filter filament penetration ranges from 9% to 24% in the inferior vena cava; filaments may even exit the vena cava to enter the aorta. 12 Tadakoshi et al 9 found that stent filament penetration triggered aortic dissection during treatment of a distal-arch thoracic aortic aneurysm. We speculate that two factors trigger PVW.…”
Section: Discussionmentioning
confidence: 99%
“…12 Tadakoshi et al. 9 found that stent filament penetration triggered aortic dissection during treatment of a distal-arch thoracic aortic aneurysm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation